Computational multi-epitope based design of a multivalent subunit vaccine against co-infecting African swine fever virus and porcine circovirus type 2 - Lauren Emily Fajardo; Edward C. Banico; Ella Mae Joy S. Sira; Nyzar Mabeth O. Odchimar; Fredmoore L. Orosco (Veterinary Integrative Sciences)
African swine fever virus (ASFV) and porcine circovirus type 2 (PCV2) are two prevalent and economically significant viruses causing high rates of pig mortality and large-scale losses to global pork production. Since there is currently no vaccine simultaneously targeting both viruses, this study aimed to computationally design a safe, stable, and effective multi-epitope based multivalent subunit vaccine against co-infecting ASFV and PCV2. Cytotoxic T-lymphocyte (CTL), helper T-lymphocyte (HTL), and linear B-lymphocyte (LBL) epitopes were screened from sequences of the Rep, Cap, and ORF3 PCV2 proteins. PCV2 epitopes predicted to be antigenic, non-allergenic, and non-toxic were linked to previously screened ASFV epitopes and Vibrio vulnificus FlaB flagellin as an adjuvant to create the final vaccine construct, which underwent physicochemical assessment and structure prediction. The vaccine construct was predicted to be stable, soluble, non-cross-reactive, antigenic, and nonallergenic. An immune simulation demonstrated that the vaccine could elicit robust antibody, T-cell, and B-cell responses. The vaccine construct stably docked to TLR5 and formed significant molecular interactions. A 200-ns molecular dynamics simulation showed that the vaccine-TLR5 complex exhibited stability and compactness throughout the run. These results show that the designed vaccine is safe, stable, and effective and warrants experimental validation.